Analisis Hubungan antara Strong Boards dan External Governance terhadap Accounting Restatement - Citra Yuristisia; Niki Lukviarman (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
This study aimed at identifying the relationship between the existence of strong boards and external governance to accounting restatement. The strong boards were characterized and identified by board independence, audit independence, and board size. External governance is identified by B-Index that found by Gompers, Ishii, and Metrick (2003). The strong boards, was measured based on good corporate governance codes developed by KNKG (2006). Data are taken from annual report from 2003 until 2006 manufacturing companies listed in Indonesian Stock Exchange. The result shows that there is a positif relationship between strong boards and external governance to accounting restatement for large firm (measured by total assets). However, the study also found that there is negative relationship between strong boards and external governance to accounting restatement for small firm as measured by total assets.Keyword: strong boards, external governance, accounting restatement, B-Index, board independence